Dampak Manajemen SDM dalam Meningkatkan Performa Karyawan - Permata, Syabina; Mardatillah, Nadya; Diningrat, Surya Jaya; Mulyadi, Mulyadi (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
To enhance organizational effectiveness, it is essential to fully leverage all available assets, particularly human assets. Consequently, human resources hold significant value for any enterprise. The management of human resources is tasked with ensuring that every individual within the organization collaborates harmoniously to optimize the organization's performance. This study seeks to evaluate the role of human capital management in improving organizational performance. effectiveness. Employing a qualitative methodology, the study examines the interplay between Miles and Huberman. Qualitative analysis is conducted on ongoing, interactive datasets to achieve data saturation. The analytical process includes three primary phases: data reduction, data distribution, and conclusions. Effective human resource management fosters a productive work atmosphere and guarantees that the company possesses a competent and highly qualified workforce. This empowers the organization to tackle challenges, boost competitiveness, and attain success.